3D pharmacophore model studies on ACRB efflux pump inhibitors of Escherichia coli : Final Report Topics Student Science Research Program In 2020 / Tran Thuy Vy ; Phan Thien Vy science instructor - Tran, Thuy Vy
Code: KD 2020.21